Penerapan Sistem General Rules dan Special Rules dalam Undang-Undang Khusus - Dianita Rahma Nugraheni; Pujiyono Pujiyono (Criminal of Law Department, Faculty of Law, Pattimura University, 2022)
The essence of criminal law reform is the renewal of intellectual conceptions or philosophical activities. The implementation of the integrated system between